Analisis Penanganan Bahan Berbahaya dalam Mempertahankan Tingkat Keselamatan dan Keamanan Pekerja di PT. Merpati Maintanance Facility Surabaya - Alvian Dwi Yulianto; Lilies Esthi Riyanti; A Nugroho Budi Rukisman (Langit Biru: Jurnal Ilmiah Aviasi, 2021)
This research purpose is completing the safety management system document of PT. Merpati Maintenance Facility Surabaya. The method used in this study is to use R&D (Research and Development) and HIRAM (Hazard Identification, Risk Assessment and Mitigation) as a form of data processing and assessment of facilities and activities so that mitigation can be carried out to reduce the high level of hazard risk on a job to be acceptable. From the research results, there are several work activities that have hazard risk values in tolerable areas so that mitigation needs to be done on the work. The conclusion of this research is that there are several hazards that have high values so that control must be carried out to reduce the risk of hazards. It is recomended to PT. Merpati Maintenance Facility to carry out all mitigation in order to make hazards in the tollerable area can move to an acceptable area.This research purpose is completing the safety management system document of PT. Merpati Maintenance Facility Surabaya. The method used in this study is to use R&D (Research and Development) and HIRAM (Hazard Identification, Risk Assessment and Mitigation) as a form of data processing and assessment of facilities and activities so that mitigation can be carried out to reduce the high level of hazard risk on a job to be acceptable. From the research results, there are several work activities that have hazard risk values in tolerable areas so that mitigation needs to be done on the work. The conclusion of this research is that there are several hazards that have high values so that control must be carried out to reduce the risk of hazards. It is recomended to PT. Merpati Maintenance Facility to carry out all mitigation in order to make hazards in the tollerable area can move to an acceptable area.